Metodyka doboru informatycznych narzędzi wspomagających controlling - Kes, Zdzisław; Nowosielski, Krzysztof (Methodology of selection of controlling information tools, 2009)
This paper describes the methodology of selections of information systems which help to use controlling. The main element of this tool is the algorithm of scaling. These questions have been applied in the form of Internet service www.cac.info.pl. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu, 2009, Nr 53, s. 29-37